2018
DOI: 10.1097/ajp.0000000000000583
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolite Changes in the Anterior Cingulate Cortex of Chronic Low Back Pain Patients and Correlations Between Metabolites and Psychological State

Abstract: Lower NAA levels and higher Glx/creatine and Glx/myoinositol ratios in the ACC of CLBP participants compared with controls were revealed. The result suggests the hypothesis that excessive Glx leads to neuronal dysfunction and/or death, which was reflected as a low NAA level in the ACC of individuals with CLBP. Measurement of these metabolites using MRS potentially helps evaluate CLBP patients' condition and psychological status objectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 53 publications
4
29
0
Order By: Relevance
“… 19 , 20 Moreover relatively low levels of NAA are also found in some chronic conditions that have chronic pain components, including diabetic painful neuropathy, chronic neuropathic pain, and chronic low back pain. 11 , 12 , 21 Thus, it is reasonable to hypothesize that individuals with chronic pain might have lower concentrations of NAA in the ACC, relative to healthy participants. 11 , 12 Consistent with a role for this metabolite in chronic pain, research has found a positive correlation between NAA levels and pain thresholds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 , 20 Moreover relatively low levels of NAA are also found in some chronic conditions that have chronic pain components, including diabetic painful neuropathy, chronic neuropathic pain, and chronic low back pain. 11 , 12 , 21 Thus, it is reasonable to hypothesize that individuals with chronic pain might have lower concentrations of NAA in the ACC, relative to healthy participants. 11 , 12 Consistent with a role for this metabolite in chronic pain, research has found a positive correlation between NAA levels and pain thresholds.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 21 Thus, it is reasonable to hypothesize that individuals with chronic pain might have lower concentrations of NAA in the ACC, relative to healthy participants. 11 , 12 Consistent with a role for this metabolite in chronic pain, research has found a positive correlation between NAA levels and pain thresholds. 10 However, our study found that tDCS could increase concentration levels of NAA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic pelvic pain patients had significantly lower levels of NAA/creatine (Cr) in the primary motor cortex compared with healthy patients [ 9 ]. And, chronic low back pain (CLBP) patients showed lower NAA levels and higher glutamate (Glu)+glutamine (Gln)/Cr and Glu+Gln (Glx)/mL ratios in the anterior cingulate cortex (ACC) of CLBP patients compared with controls [ 10 ]. CLBP patients showed significant decrease in Glu in patients’ ACC and reduced ml in the ACC and thalamus [ 11 ], decreased choline (Cho) in the right somatosensory cortex [ 12 ].…”
Section: Introductionmentioning
confidence: 99%